2014
DOI: 10.3342/kjorl-hns.2014.57.8.511
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Prognosis of Idiopathic Sudden Sensorineural Hearing Loss in Old Age

Abstract: Background and ObjectivesZZIn aging society, interest in idiopathic sudden sensorineural hearing loss (ISSNHL) in elderly have been increased. However, as there has been little discussion about prognostic factors of ISSNHL in old age, this study aims to investigate clinical factors related with prognosis of ISSNHL in elderly and compare with that in adults. Subjects and MethodZZA retrospective medical chart review was performed in patients over 19 years old who diagnosed with ISSNHL from Jan. 2010 to Dec. 2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…However, individuals in the 0–12‐month group had the highest risk of CCVD, which could indicate that SSNHL could have occurred earlier than the first official diagnosis. Therefore, it is necessary to check patient history for an accurate diagnosis; however, in the case of older individuals, they often cannot remember it accurately 22 ; highlighting the possibility that the disease could have occurred earlier than the official diagnosis. Furthermore, those who suffer from SSNHL may have trouble communicating with others, resulting in decreased cognition, anxiety, depression, and social isolation 23 .…”
Section: Discussionmentioning
confidence: 99%
“…However, individuals in the 0–12‐month group had the highest risk of CCVD, which could indicate that SSNHL could have occurred earlier than the first official diagnosis. Therefore, it is necessary to check patient history for an accurate diagnosis; however, in the case of older individuals, they often cannot remember it accurately 22 ; highlighting the possibility that the disease could have occurred earlier than the official diagnosis. Furthermore, those who suffer from SSNHL may have trouble communicating with others, resulting in decreased cognition, anxiety, depression, and social isolation 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these studies did not find any significant factors associated with hearing recovery [ 43 , 44 ]. However, other studies, which have compared elderly patients to control groups (younger individuals), have reported significantly lower hearing recovery rates among the elderly population [ 45 , 46 ]. Additionally, these studies have indicated that the timing of treatment initiation and the hearing status of the contralateral ear play a role in the prognosis of SSNHL in elderly patients [ 45 , 46 ].…”
Section: Treatmentmentioning
confidence: 99%
“…However, other studies, which have compared elderly patients to control groups (younger individuals), have reported significantly lower hearing recovery rates among the elderly population [ 45 , 46 ]. Additionally, these studies have indicated that the timing of treatment initiation and the hearing status of the contralateral ear play a role in the prognosis of SSNHL in elderly patients [ 45 , 46 ]. In a study comparing 40 patients aged 65 years or older with 40 relatively younger patients (aged 55–64 yeasrs), there were no significant differences in hearing status or underlying conditions between the elderly and control groups [ 47 ].…”
Section: Treatmentmentioning
confidence: 99%